Providensia Allah dalam Kitab Ayub - Tri Subekti (REDOMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2022)
control of every human life, history, existence and order of the universe. God's extraordinary involvement in human life, especially in the book of Job, is in the form of providence or God's care and provision for Job. The book of Job discusses how Job experienced God's extraordinary providence in his life and family. The author uses the literature study method to describe the form of God's providence in the book of Job. Through literature studies by reading books, the author can formulate a useful view of the existence of God in the book of Job. AbstrakAllah menguji iman seseorang melalui masalah yang datang bertubi-tubi dalam kehidupan. Allah berdaulat dan memegang kendali atas kehidupan setiap manusia, sejarah, keberadaan dan tatanan alam semesta. Keterlibatan Allah yang luar biasa dalam kehidupan manusia khususnya dalam kitab Ayub yaitu berupa providensia atau pemeliharaan dan penyediaan Allah terhadap Ayub. Kitab Ayub membahas bagaimana Ayub mengalami providensia Allah yang luar biasa dalam hidup dan keluarganya. Penulis menggunakan metode studi literatur untuk mendiskripsikan bentuk providensia Allah dalam kitab Ayub. Melalui kajian Pustaka dengan membaca buku-buku maka penulis dapat merumuskan suatu pandangan yang bermanfaat tentang proidensia Allah dalam kitab Ayub.